ANALYSIS OF NEWS ITEM TEXT FOUND IN ??THE JAKARTA POST? ENTITLED; ??Boat People May Be Allowed to Pass RI Waters? - Mahalli Mahalli (Universitas Islam Nahdlatul Ulama Jepara, 2013)
ABSTRACTThe questions of this study are what types of Processes found in newspaper reports, why the dominant Process used to develop the genre and what genre is used to realize the discourse. The object of this study is news taken from the Jakarta Post online entitled Boat People May Be Allowed to Pass RI Waters published on Monday, November 25, 2013, 1:15 PM. In this study, the writer concerned on functional grammar, mainly on ideational meaning. In order to get the objective of this study, the writer used some theories related to the literature, discourse, genre, grammar and ideational meaning itself. In the Process type analysis, there were four types of processes found in the news and the most process appeared was material process. The Material Process expressed in past tense. It means the text is retelling about a sequence of happening or informing something. The writer also found that there was news item genre, instead of recount, which dominate the text entitled Boat People May Be Allowed to Pass RI Waters published on Monday, November 25, 2013, 1:15 PM .Finally, the writer found that Material Processes which expressed in past tense used to reconstruct news item text that developed Boat People May Be Allowed to Pass RI Waters. Keywords: Genre, Text Analysis, News Paper ABSTRAKPertanyaan penelitian ini adalah apa jenis proses yang ditemukan dalam laporan surat kabar, mengapa proses dominan digunakan untuk mengembangkan genre, dan apa genre yang digunakan untuk mewujudkan wacana tersebut. Objek penelitian ini adalah berita yang diambil dari Jakarta Post secara online berjudul ??Boat People May Be Allowed to Pass RI Waters? diterbitkan pada Senin 25 November, 2013, 01:15. Dalam penelitian ini, penulis bersangkutan pada tata bahasa fungsional, terutama pada makna ideasional. Dalam rangka untuk mendapatkan tujuan penelitian ini, penulis menggunakan beberapa teori yang berkaitan dengan sastra, wacana, genre, tata bahasa dan makna ideasional itu sendiri. Dalam analisis tipe proses, ada empat jenis proses yang ditemukan dalam berita dan proses yang paling muncul adalah proses material. Proses Material dinyatakan dalam past tense. Arti teks tersebut adalah menceritakan kembali tentang urutan terjadi atau menginformasikan sesuatu. Penulis juga menemukan bahwa ada berita genre; recount, yang mendominasi teks berjudul ??Boat People May Be Allowed to Pass RI Waters? diterbitkan pada Senin 25 November, 2013, 01:15.Akhirnya, penulis menemukan bahwa Proses Material yang disajikan dalam past tense digunakan untuk merekonstruksi berita teks yang dikembangkan ??Boat People May Be Allowed to Pass RI Waters?.Kata-kata Kunci : Genre, Analisis Teks, Koran